2015
DOI: 10.9734/jsrr/2015/14515
|View full text |Cite
|
Sign up to set email alerts
|

Sensory Profile and Consumer Acceptability of Ziziphus mauritiana and Processing Product in Savannah Region of Cameroon

Abstract: Aim: Ziziphus mauritiana is an endemic fruit spread in the savannah region of Cameroon. The fruit, locally called Jaabi, is harvested dry and consumed as such or processed into a local cake named Yaabande, using three baking techniques (sun drying, steam baking and stifle baking). The aim of the study is to characterize the sensory profile and consumer acceptability of the fruit and its processed product, in order to evaluate the determinant of their quality attributes as influenced by ecotype, origin and proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Conversely, results in Guinea and Mali showed that local rice was preferred for its taste and freshness (Rutsaert et al., 2013). A number of articles have been published on consumer acceptability of local products using hedonic test (Adinsi et al., 2015; Akissoé et al., 2015; Bechoff et al., 2014; Neville et al., 2017; K. Tomlins et al., 2007; Touwang et al., 2015). In the last decades, check‐all‐that‐apply (CATA) question has been widely used to provide valid sensory characterization of many different foods.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, results in Guinea and Mali showed that local rice was preferred for its taste and freshness (Rutsaert et al., 2013). A number of articles have been published on consumer acceptability of local products using hedonic test (Adinsi et al., 2015; Akissoé et al., 2015; Bechoff et al., 2014; Neville et al., 2017; K. Tomlins et al., 2007; Touwang et al., 2015). In the last decades, check‐all‐that‐apply (CATA) question has been widely used to provide valid sensory characterization of many different foods.…”
Section: Introductionmentioning
confidence: 99%